Properties of poly(lactic acid) nanocomposites based on montmorillonite, sepiolite and zirconium phosphonate - K. Fukushima; A. Fina; F. Geobaldo; A. Venturello; G. Camino (eXPRESS Polymer Letters)
Poly(lactic acid) (PLA) based nanocomposites based on 5 wt.% of an organically modified montmorillonite (CLO), unmodified sepiolite (SEP) and organically modified zirconium phosphonate (ZrP) were obtained by melt blending. Wide angle X-ray scattering (WAXS) and scanning electron microscopy (SEM) analysis showed a different dispersion level depending on the type and functionalisation of nanoparticles. Differenctial scanning calorimetric (DSC) analysis showed that PLA was able to crystallize on heating, and that the addition of ZrP could promote extent of PLA crystallization, whereas the presence of CLO and SEP did not significantly affect the crystallization on heating and melting behaviour of PLA matrix. Dynamic Mechanical Thermoanalysis (DMTA) results showed that addition of all nanoparticles brought considerable improvements in E' of PLA, resulting in a remarkable increase of elastic properties for PLA nanocomposites. The melt viscosity and dynamic shear moduli (G',G") of PLA nanocomposites were also enhanced significantly by the presence of CLO and SEP, and attributed to the formation of a PLA/nanoparticle interconnected structure within the polymer matrix. The oxygen permeability of PLA did not significantly vary upon addition of SEP and ZrP nanoparticles. Only addition of CLO led to about 30% decrease compared to PLA permeability, due to the good clay dispersion and clay platelet-like morphology. The characteristic high transparency of PLA in the visible region was kept upon addition of the nanoparticles. Based on these achievements, a high potential of these PLA nanocomposites in sustainable packaging applications could be envisaged.